Sosialisasi Permainan Softball Pada Guru Pjok Sekolah Dasar Sekecamatan Tilamuta Kabupaten Boalemo - Lamusu, Zulkifli; Lamusu, Ahmad (Universitas Negeri Gorontalo, 2026)
This community service program aims to strengthen the pedagogical understanding and professional readiness of elementary school Physical Education, Sports, and Health (PJOK) teachers through the socialization of adaptive softball games as an alternative learning material. The activity was conducted in Tilamuta District, Boalemo Regency, Gorontalo Province, involving elementary school PJOK teachers as participants. The implementation method employed an educational and participatory approach, including the delivery of basic concepts of softball games, guided discussions, simulation of modified game practices, and collective reflection. The results indicate that the socialization of adaptive softball games contributed positively to improving teachers’ understanding of the potential of softball as a safe, enjoyable, and developmentally appropriate learning material for elementary school PJOK. Teachers recognized that softball can be developed through modifications of rules, equipment, and activity formats to support the mastery of fundamental movement skills while simultaneously fostering character values such as cooperation, sportsmanship, discipline, and responsibility. The active participation of teachers throughout the activities demonstrates the effectiveness of an experiential-based approach in supporting the professional development of PJOK teachers. This program is aligned with the principles of the Merdeka Curriculum, which emphasizes meaningful and student-centered learning.